Modeling the Determinants of Islamic Banking Adoption Among Indonesian Civil Servants: A Multigroup Structural Equation Modeling Approach - Zulfikar Hasan (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2026)
Background: Despite Indonesia being the world’s largest Muslim-majority country, the penetration of Islamic banking remains low, especially among civil servants who represent a strategic and financially literate segment. Limited understanding of behavioral, technological, and trust-related factors constrains the expansion of Islamic banking in this group. Objectives: This study aims to model the determinants influencing Sharia banking adoption among Indonesian civil servants by examining the effects of religiosity, perceived usefulness, service quality, trust, social influence, and financial literacy on behavioral intention and actual usage behavior. Novelty: The study integrates the Theory of Planned Behavior (TPB), the Technology Acceptance Model (TAM), and trust-based frameworks into a unified model specifically tailored for public-sector employees. It contributes to the literature by offering empirical evidence on Islamic banking adoption within an underexplored yet influential demographic segment. Research Methodology / Design: A quantitative approach using Structural Equation Modeling (SEM) and Multigroup Analysis (MGA) was employed. Data were obtained through a nationwide survey of 412 civil servants representing diverse educational and employment backgrounds. Findings: Trust and religiosity emerged as the strongest determinants of adoption intention, followed by perceived usefulness, service quality, financial literacy, and social influence. Behavioral intention significantly affected actual usage. Multigroup analysis revealed gender, education, and institutional differences in adoption behavior. Implications: The study advances theoretical understanding of Islamic banking adoption and offers practical insights for policymakers and Islamic financial institutions to enhance financial literacy, trust, and service quality among civil servants.